Model Layanan Klasikal Teknik Home Room Berbasis Onlien Mengurangi Fomo Menggunakan Media Sosial - Desy Mustika; Akhmad Rizkhi Ridhani; Farial Farial (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
The research gave birth to a classic service development model for online-based homeroom techniques to reduce the feeling of FoMo in using social media in the people of South Kalimantan. The impact of the pandemic requires staying at home while most people spend time at home playing smartphones and accessing social media. Inappropriate use of social media triggers a sense of FoMO in using social media. This research is an R&D research with modified development procedures, namely preliminary studies, model development, model validation tests, and model revisions. This is to determine the condition of the community experiencing FoMO based on the results of interviews and observations. The form of the model developed has gone through expert and practitioner validation tests. Keywords: Fomo, Classical Services, Homeroom Engineering